Mesures climatiques aux échelles fines (météorologiques et agronomiques) et variabilité spatiale du gel printanier dans le vignoble de Vinho Verde (Portugal) - Quénol, Hervé (2004)
In the Entre Douro e Minho area (North of Portugal)two distant vineyards (which different topography and grapes are studed from a agroclimatological perspective. The objective is to determine the optimal topoclimatic conditions for the culture of the vine. A climatic study on fine scales is carried out in order to determine the local influence of the surface characteristics on the weather parameters. The temperature measurements and the agronomic analysis carried out between February and April 2003 showed a strong space-time variability of the spring frost risk between the two sites and inside even of the soils.